Wheat fiber colored with a safflower (Carthamus tinctorius L.) red pigment as a natural colorant and antioxidant in cooked sausages. Issue 1 (November 2015) - Kim, Hyun-Wook; Hwang, Ko-Eun; Song, Dong-Heon; Kim, Yong-Jae; Ham, Youn-Kyung; Lim, Yun-Bin; Jeong, Tae-Jun; Choi, Yun-Sang; Kim, Cheon-Jei
Abstract This study was conducted to evaluate the effects of nitrite and wheat fiber (WFC) colored with a safflower (Carthamus tinctorius L.) red pigment on the color characteristics and lipid oxidation of cooked sausages. The safflower red pigment (carthamin) was extracted at alkali condition, and wheat fiber was colored with the extracted safflower red pigment. Total six cooked sausage treatments were prepared with two nitrite levels (0 and 120 ppm) and three WFC levels (0, 1, and 2%). As the WFC level was increased, redness of cooked sausages increased, regardless of presence/absence of nitrite. Carthamin contained in WFC could promote a reaction and/or decomposition of nitrite, resulting in increased nitrosoheme pigment and decreased residual nitrite. In addition, WFC inhibited lipid oxidation of cooked sausages. Consequently, the addition of WFC resulted in positive effects on color formation, residual nitrite, and lipid oxidation, as well as the improvement cooking yield of cooked sausages. Therefore our result suggested that WFC could be possible to partially replace nitrite and coloring of dietary fiber with natural pigments is a useful technique to expand the purposeful use of dietary fiber.